Analisis Kemampuan Berpikir Komputasi Siswa Dalam Menyelesaikan Soal Bangun Ruang Sisi Datar Ditinjau Dari Self Confidence - Nurhayati, Siti; Maharani, Hevy Risqi; Basir, Mochamad Abdul (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2025)
Computational thinking is one of the thinking skills needed in the 21st century. This research aims to describestudents' computational thinking skills in solving problems on polyhedrons in terms self-confidence. Individualself-confidence can influence students' way of thinking when solving problems. This research method uses aqualitative descriptive approach. Data collection techniques used questionnaires and tests for 29 class VIIIstudents and interviews with 2 students for each category of high, medium, and low self-confidence. Thisresearch data analysis includes data collection, data reduction, data presentation, and drawing conclusions.The results of the research show that students' computational thinking abilities in solving flat-sided geometricproblems with students with high self-confidence are able to achieve indicators of decomposition, patternrecognition, algorithmic thinking, generalization and abstraction. Students with moderate self-confidence areable to achieve indicators of decomposition, pattern recognition and generalization and abstraction, but are lesscapable in algorithmic thinking. Students with low self-confidence are less capable in decomposition indicatorsand have not been able to achieve indicators of pattern recognition, algorithmic thinking and generalization andabstraction.